Evolution of Tatarstan’s Local Self-Governments and Challenges They Face - Refly Setiawan (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: The laws in the Republic of Tatarstan tend to limit the powers and coverage of local self-government, but Tatarstan’s laws go even further than most in maintaining the “power vertical” which allows state authorities to keep tight control of local self-governments. This control is exercised officially through the laws, and in practice, with financial controls. The local self- governments have difficulty with self financing and are left beholden to state authorities. Because the heads of the 43 administrative districts and 11 large cities in Tartarstan are directly appointed by the president, he exercises rigid control all the way down to the local level. In addition, because these administration heads are allowed to run for parliament, the president has also consolidated considerable power on the level of the republic’s government. In effect, government on the level of the administrative districts and large cities in the republic is completely in the hands of the president and his appointees, who also have financial control over local self- governments.Keywords: Evolution, Tatarstan Local Government, Challenges Faced Abstrak:Undang-undang di Republik Tatarstan cenderung membatasi kekuasaan dan cakupan pemerintahan setempat, tetapi undang-undang Tatarstan bahkan lebih jauh daripada kebanyakan undang-undang lainnya dalam mempertahankan